2019
DOI: 10.1093/mnras/stz1132
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation for scarce stellar populations

Abstract: We present a Bayesian method to determine simultaneously the age, metallicity, distance modulus, and interstellar reddening by dust of any resolved stellar population, by comparing the observed and synthetic color magnitude diagrams on a star by star basis, with no need to bin the data into a carefully selected magnitude grid. We test the method with mock stellar populations, and show that it works correctly even for scarce stellar populations with only one or two hundred stars above the main sequence turn off… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The case of galaxies with several bursts of star formation but poorly populated CMDs is particularly challenging since the number of free parameters is large enough to make binning methods unappealing (Ramírez-Siordia et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of galaxies with several bursts of star formation but poorly populated CMDs is particularly challenging since the number of free parameters is large enough to make binning methods unappealing (Ramírez-Siordia et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The variety of age estimates for the stars in this galaxy motivates our study. To characterize the SFH of Eri II we avoid the isochrone fitting to the CMD and other data binning techniques, especially unappealing for sparse populations, that have been used frequently in the literature (Ramírez-Siordia et al 2019). We opt for Bayesian inference, which allows us to estimate not only the physical parameters describing a stellar population but also their uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…There are no differences between the isochrones in the databases employed in SIRIUS for the faintest stars (∼ 2 magnitudes below the TO), therefore the fit does not depend on the faintest stars. Ramírez-Siordia et al (2019) presented an analysis considering the faintest stars. They concluded that the effect of faintest stars only increases the uncertain-ties without changing the mode of distribution, since the isochrones do not seem to be different for the faintest stars, as shown in Figure 2 (third panel).…”
Section: Sources Of Uncertaintymentioning
confidence: 99%
“…The total likelihood ln P(M|D) is a linear combination of the priors and the likelihood of each stellar population with influence of SSP parameters: where f [i]G represents the fraction of stars that belong to the i-th population. A similar likelihood based on MPs and weighted by the fraction of stars is applied in Ramírez-Siordia et al (2019).…”
Section: Age Difference ∆τmentioning
confidence: 99%
See 1 more Smart Citation